STRENGTHENING ACADEMIC CULTURE THROUGH LEARNING ORGANIZATIONS AMONG NON-MUSLIM STUDENTS - Asep Kusmawan; Deka Meuthia Novari; Rusyati Prihatin (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
Higher education institutions are required to transform themselves into adaptive learning organizations in order to remain relevant to the needs of the times and to strengthen academic culture. This study aims to analyze the strengthening of academic culture among non-Muslim students at the Al-Ma'arif Way Kanan Institute through learning organizations, as well as to identify factors that hinder and support the strengthening of academic culture on campus. This study uses qualitative research. The data collection methods used interviews and observations with Miles and Huberman data analysis. The results show that the strengthening of the learning organization's academic culture at the Al Ma'arif Way Kanan Institute is achieved through active participation in the learning process, involvement in seminars and scientific forums, a culture of sharing and collective learning, and an inclusive academic climate. The inhibiting factors in improving academic culture include the limited time of educators, low student motivation in participating in academic activities, and holiday policies that limit the optimization of academic programs. Analysis of the strengthening of academic culture through learning organizations shows an increase in the academic activities of non-Muslim students, marked by the courage to argue critically and the ability to think at a high level. Participation in seminars and scientific forums expands learning to the realm of real-world experience and strengthens team learning and organizational learning. In addition, the culture of sharing references and interfaith study groups affirms the development of shared learning in the academic environment. This study contributes to enriching the study of learning organizations in the context of inclusive religious universities and offers models and policy implications for strengthening an adaptive academic culture among students